Ethionine-resistant mutants of the filamentous blue-green alga Plectonema boryanum. - Hentschel, W M (1978)
Plectonema boryanum mutants that are resistant to ethionine are unable to incorporate ethionine into acid-precipitable material. Ethionine causes bleaching of chlorophyll in sensitive cells.